2016
DOI: 10.1016/j.ces.2016.06.040
|View full text |Cite
|
Sign up to set email alerts
|

A PIV investigation of the effect of disperse phase fraction on the turbulence characteristics of liquid–liquid mixing in a stirred tank

Abstract: In this paper, utilizing 2D angle-resolved particle image velocimetry (PIV), the flow field of a dilute aqueous-in-oil dispersion is experimentally studied in a stirring tank. Opacity during liquid-liquid mixing is eliminated by matching the refractive indices of both phases. Anisotropy of the turbulence flow field is analysed via the turbulent kinetic energy (TKE) and energy dissipation rate (EDR) obtained at different measuring angles. The influence of spatial resolution is compared and discussed. TKE and ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
2
17
0
12
Order By: Relevance
“…The fluid flow in single or multiphase systems can be analyzed by various measurement techniques. Field and volume information can be achieved by imaging techniques using tracers, color changes as well as particle image velocimetry (PIV) , , laser‐induced fluorescence (LIF) or tomographic methods including combined solutions such as tomographic PIV , . Single point measurements are possible for example with hot‐wire anemometry, laser‐Doppler velocimetry (LDV) or ultrasound doppler velocimetry .…”
Section: Particle Swarm Characterizationmentioning
confidence: 99%
“…The fluid flow in single or multiphase systems can be analyzed by various measurement techniques. Field and volume information can be achieved by imaging techniques using tracers, color changes as well as particle image velocimetry (PIV) , , laser‐induced fluorescence (LIF) or tomographic methods including combined solutions such as tomographic PIV , . Single point measurements are possible for example with hot‐wire anemometry, laser‐Doppler velocimetry (LDV) or ultrasound doppler velocimetry .…”
Section: Particle Swarm Characterizationmentioning
confidence: 99%
“…These particles are characterized by a considerable value of the refractive index, as it is equal to 1.5. Due to the above characteristics, in many works [13,14,15], PSP particles are recommended for applications in systems including water phase flow in particular for the case of the complex stream trajectory. In order to obtain a constant water homogenization with seeding particles, an agitator was installed in the tank.…”
Section: Measurement Setup and Methodologymentioning
confidence: 99%
“…Zhang et al studied the turbulence kinetic energy dissipation rate and turbidity near the coast of East China Sea and concluded that the ocean mixing process has a mean turbulence kinetic energy dissipation rate of 5.7 ϫ 10 Ϫ5 W/kg (Zhang et al, 2016). Liu et al analyzed the anisotropy of the turbulence flow field via the turbulence kinetic energy and energy dissipation rate (Liu et al, 2016). The ocean turbulence leads to the dissipation and mixing of ocean populations; thus, the flow sensors used in ocean turbulence environment should have a low kinetic energy dissipation rate.…”
Section: Introductionmentioning
confidence: 99%